From buffalo to human: Klebsiella pneumoniae in high-somatic cell count milk as an overlooked link in the one health chain - Zhifei Wei; Yifei Xiang; Xuelian Mo; Wenjing Li; Erqiang Wang; Changhua Lin; Jiazhou Wei; Yulian Xi; Yuying Liao; Zhengmin Liang; Zhiran Xu; Jiakang He (International Journal of Food Microbiology, 2026)

Nicotine-induced mitophagy in bronchial epithelial cells and MYST1 downregulation in cigarette smoke–exposed lungs: potential mechanisms of COPD progression - Kai Liu; Dongchuan Xu; Jie Zhao; Rubing Mo; Mei Lin; Chanyi He; Qi Lin; Tian Xie; Quanni Li; Yipeng Ding (Molecular Biology Reports, 2026)

Identification of novel loci regulating circulating melatonin and its causal relationship with hypertension - Lin Yan; Yang Qiu; Zhiwen Mo; Mingli Li; Xueran Huang; Yongfen Gao; Boteng Yan; Qiantu Hu; Haiying Zhang; Zengnan Mo; Rui Lin (Human Genetics, 2026)

Farrerol improves the maturation quality of porcine oocytes derived from small follicles associated with RAD51-related DNA repair responses - Lin Qi; Yingting Pan; Chaoqun Qu; Shuangyan Mo; Cuiting Peng; Hao Xie; Yulan Zhao; Yijie Tang; Wei Shen; Zhilong Chen; Zhonglin Tang (Theriogenology, 2026)

Aromatic protein-like recognition enables rapid prediction of sludge deep dewaterability - Jianting Liu; Zhihua Mo; Qingyi Lei; Haowen Guo; Shengye Lin; Zhijian Fu; Jialin Liang; Shuiyu Sun (Bioresource Technology, 2026)

Synergistic CO2 capture by a novel 2 M 1-(2HE)PP/3 M AEEA blends: Performance evaluation and mechanistic insights - Qixin Li; Dingkai Hu; Haoyang Lin; Dezhi Cao; Yingshuang Zhang; Shaoyun Chen; Wenlong Mo (Journal of Environmental Chemical Engineering, 2026)

2,6-Dibromophenol inhibits fin regeneration in zebrafish larvae via Wnt-mediated immune cell recruitment - Yuhan Huang; Wenya Tie; Zijian Li; Nannan Wang; Jiayan Xiong; Li Lin; Yuan Kong; Yunyi Mo; Minting Li; Jianpeng Liu; Zhonghao Xiao; Weitao Hu; et al. (Fish & Shellfish Immunology, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Illicium verum polysaccharide targets fimbriae and flagella to disrupt biofilm and inhibit multidrug-resistant Escherichia coli proliferation - Yifei Xiang; Erqiang Wang; Xuelian Mo; Zhifei Wei; Zhiran Xu; Wenjing Li; Changhua Lin; Yanwen Zhang; Chunxia Ma; Bin Zheng; Ziyang Li; Chengzhi Liu; et al. (Carbohydrate Polymers, 2026)

Autocatalytic DNA nanosphere assembly activated by endogenous APE1 for intracellular miR-21 imaging - Liuting Mo; Chunfen Zhang; Rongzheng Yuan; Yan Hong; Chan Yang; Weiying Lin (Analytica Chimica Acta, 2026)

Regenerable Cu2S-CuO heterostructure nanoarray electrode for efficient electrochemical iodate reduction - Yingshuo Wu; Youkui Zhang; Jiahao Mo; Fuping Zhou; Yuanli Li; Lin Zhu; Tao Duan (Journal of Hazardous Materials, 2026)

Investigation of micro- and macro-scale fracturing mechanisms in sandstone exposed to freeze-thaw cycles using DEM simulations and theoretical analysis - Barkat Ullah; Zilong Zhou; Dagan Lin; Hanfeng Zhang; Fanjunhui Mo; Fushen Liu (Geomechanics for Energy and the Environment, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Transforming waste copper slag into a nitrogen-doped mesoporous catalyst for singlet oxygen-dominated peroxymonosulfate activation toward efficient and sustainable degradation of rhodamine B - Ying Zhang; Chunjie Huang; Ying Lin; Xingyong Xue; Lihong Lan; Yaocong Han; Qiaoqiao Su; Jinlu Liang; Dongping Wei; Linqiang Mo (Environmental Research, 2026)

Fire severity alters soil microbial diversity and community stability in a subtropical forest ecosystem - Yuan Tang; Tongjian Zi; Xiaona Li; Jiayao Zhang; Shuyi Lin; Yunjia Mo; Bin Tian; Xuezhao Wang (CATENA, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

Storm surge forecasting using TCWiSE synthetic typhoons with an LSTM model - Cheng Chen; Jianxiang Mo; Hongkun Lin; Fengyi Li (Ocean Engineering, 2026)

Osteoprotective effect of Perinereis aibuhitensis ultrasound-assisted aqueous extract against retinoic acid-induced osteoporosis in mice - Biliang Mo; Xinxia Song; Jianmeng Liao; Xiaoyu Xia; Hongyu Lu; Wenhong Cao; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Zhihong Zheng; et al. (Food Bioscience, 2026)

Seismic performance and failure mechanisms of scaled reinforced concrete containment vessels under shake table testing - Chang-Ching Chang; Jiaji Wang; Chiun-lin Wu; Thomas T.C. Hsu; Kalyana B. Nakshatrala; Yi-Lung Mo (Engineering Structures, 2026)

3D-printed Li-HA composite scaffold with staged simvastatin/NGF delivery and continuous Li+ signaling enhances immune–neuro–angiogenic coupling for bone repair - Xianglei Mo; Tengbin Shi; Siyi Huang; Dongyi Mai; Lingyu Kong; Junkai Mi; Zongqiang Gao; Wenge Liu; Yanjin Lu; Tingting Huang; Jinxin Lin (Chemical Engineering Journal, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unveiling Key Factors in Determining Biodegradable Mulching Film Adoption Through Evolutionary Game Analysis - Wanying Lin; Xi Mo; Luca Nizzetto; Xuan Shi; Yuan Chen; Jinhui Li; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2026)

Fine-scale soil heterogeneity shapes compartment-specific microbial assembly and soil microbial functional differentiation in Lepturus repens on a coral island - Shengen Zhong; Shunfen Wang; Yimin He; Kaiwen Yang; Yuhang Wen; Ziyang Zhang; Mo Shi; Liaoyuan Zhang; Wenxiong Lin; Xin Qian (Plant and Soil, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Insights into the role of pyrolysis temperature in cotransport of biochar nanoparticles and polystyrene nanoplastics in porous media - Xuanhao Lin; Ming Wu; Qusheng Li; Hui Li; Yanru Hao; Cehui Mo (Journal of Environmental Sciences, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Unveiling mechanistic insights of inactivated Aspergillus niger spore by fishery-waste-derived chitosan via synchrotron radiation tomography - Ying-Chen Chen; Chih-Huang Weng; Chun-Chieh Wang; Zi-Jing Lin; Shang-Ming Huang; Girma Sisay Wolde; Jenn-Wen Huang; Mo Da-Sang Hua; Yao-Tung Lin (Carbohydrate Polymers, 2026)

Enhancing Daily Runoff Prediction Accuracy with the Coupled KAN-LSTM Model and a Dynamic Postprocessing Module - Chongxun Mo; Tao Feng; Keke Huang; Zhiwei Yan; Zihan Lin; Haiyang Wang; Jiameng Xu; Yuyi Zhong; Gang Tang; Yi Huang (Water Resources Management, 2026)

The role of the subcortical structures in subthreshold depression: evidence from static and dynamic functional connectivity - Siying Zhang; Lijun Ma; Jiangzhou Sun; Yujie Chen; Yuanyun He; Qiutong Long; Bingqing Jiao; Huiyuan Huang; Lei Mo; Jiabao Lin (Brain Structure and Function, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Cationic-functionalized tea stalk derived biochar for Cr(VI) remediation in environmental media: Synergistic reduction-adsorption mechanisms and environmental application - Jianhua Qu; Xuerui Liu; Chunying Lin; Jia Qi; Wei Peng; Enyang Mo; Haiyi Zhang; Tianqi Liu; Ying Zhang (Journal of Environmental Chemical Engineering, 2026)

Ultrafast degradation of mineral processing collector via magnetic Fe3O4/graphene oxide activating peroxydisulfate: Performance and mechanism - Zequan Lin; Wei Mo; Yuxin Feng; Junjie Wu; Xiujuan Su; Jinlin Yang; Yuhua Huang; Jinpeng Feng; Shaojian Ma (Journal of Environmental Chemical Engineering, 2026)

Assessment of oligosaccharide addition on in vitro digestion, hydrolysate absorption, and in vivo digestive enzyme activity of milk/soy proteins - Qiaoya Mo; Tao Lin; Yihan Lin; Chang Xu; Xin Rui; Wei Li (Food Chemistry, 2026)

A carboxymethyl cellulose-based hydrogel sensor that can monitor surface compressive force and blue light-activated antibacterial properties in real time, used for preserving loquats - Yuluo Zheng; Qi Mo; Xuyang Lu; Jianming Lin; Jiaxin Cai; Shuang Tian; Yingying Yang; Zehao Huang; Chongxing Huang; Lijie Huang (Food Control, 2026)

Antiviral activity of marine fungal polysaccharide AVP141-A against Singapore grouper iridovirus (SGIV) in vitro and in vivo - Xinyu Liao; Xiaohui Zheng; Li Mo; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2026)

Bio-dissolution of hazardous Cu, As, Sb and Zn from polymetallic tetrahedrite by a moderately thermophilic consortium - Xin Nong; Lin Liu; Yuguang Wang; Yufang Guo; You Li; Qiu Yi; Qiuju Mo; Chenbing Ai (Environmental Research, 2026)

Consistent neural evidence to support novelty and appropriateness processing for creative thinking: a coordinated meta-analysis using activation likelihood estimation - Jiabao Lin; Yuanyun He; Siying Zhang; Lei Mo; Changyi Kuang; Yajue Chen (Brain Structure and Function, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Moisture limitation and nocturnal insulation underpin heatwave diversity in hydroclimatic transitional zones - Ruikun Gou; Xuechun Wang; Lin Zhu; Siyuan Zhu; Yanzheng Yang; Lidong Mo (Journal of Arid Environments, 2026)

Deep eutectic solvent-based ultrasound extraction of bioactive flavonoids from Coreopsis tinctoria Nutt.: Process optimization, HPLC analysis, and preliminary bioactivity evaluation - Peng Wen-Yu; Lin Fang-Qi; Mo Hong-Bo; Hu Tong-Yi; Ou Hong (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Ultrasound-induced modifications of fish proteins: a comprehensive review of structural, physicochemical, functional properties, and industrial applications - Qingzhi Ding; R.A. Dilmi Anuththara Ranasinghe; Zijie Mo; Huamin Yang; Lin Luo; Haile Ma; Xiaoran Li; Chunhua Dai; Ting Zhang (Food Research International, 2026)

An interpretable ensemble machine learning model for predicting carbon dioxide adsorption on magnesium oxide-based sorbents - Lin Fan; Yan He; Yunfeng Mo; Yiming Cao (Environmental Research, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Mariana trench-derived fungal polysaccharide AVP214–1 inhibits Singapore grouper iridovirus infection in vitro and in vivo - Xinyu Liao; Gaoqi Yu; Xiaohui Zheng; Yanqi Zhao; Siting Wu; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Zhuang Han; Qiwei Qin; Jingguang Wei (Aquaculture, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Multigenerational impacts and health risk of environmental pollutants on fish caused by life-cycle exposure - Sutapa Debi; Jianqing Lin; Jiezhang Mo; Wenhua Liu (Marine Environmental Research, 2026)

Effects of microwave-stabilized rice aleurone layer flour (MSF) on gel properties of early-indica rice flour and semi-dried rice noodles in non-extruded and extruded systems - Yakun Song; Qing Wang; Weiling Mo; Chunmin Guan; Fan Qiao; Jianhua Zhu; Wenhua Zhou; Qinlu Lin; Chun Liu (Journal of Cereal Science, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

Long-term Nitrogen Addition Did Not Aggravate Soil Microbial Phosphorus Demand in a Tropical Forest - Xuehua Hu; Yubiao Lin; Qifeng Mo; Yingxu Fan; Faming Wang; Xiangping Tan; Qian Zhao (Journal of Soil Science and Plant Nutrition, 2026)

Zero-energy, capillarity-gravity self-filtration system: A sustainable and ultra-low cost solution for high-efficiency microalgae removal - Haochuan Lin; Junjie Yang; Yuqin An; Mo Dong; Zupei Wang; Yiqi Tang; Huanhuan Tang; Hong Yao; Xinyang Li; Wen Zhang (Chemical Engineering Journal, 2026)

Nitrogen removal driven by zonal supply of thiosulfate and pyrite in an up-flow blanket filter (UBF) reactor - Qian Zhang; Lan Lin; Tingsheng Hu; Qianyi Liu; Ying Wang; Haozhe Mo; Wenbiao Jin; Wei Zhang; Jun Chen; Huabin Zeng; Xiaojun Wang; Shaohua Chen; et al. (Bioresource Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Structural reconstruction-induced electronic Kagome lattices with low-energy flat bands in twisted double bilayer graphene - Mo-Han Zhang; Yalei Zhang; Chen-Yue Hao; Zi-Han Guo; Chao Yan; Ya-Xin Zhao; Ya-Ning Ren; Jin-Hua Gao; Shengjun Yuan; Lin He (Science Bulletin, 2026)

A novel potential toxic target of PBDEs in cetaceans: Impaired wound healing demonstrated in Indo-Pacific finless porpoise fibroblasts - Yajing Sun; Chengzhang Li; Ying Zeng; Imran Rashid Rajput; Jiashen Tian; Yuqi Wu; Juntao Ye; Ziyan Wang; Qinghong Liao; Jiezhang Mo; Zonghang Zhang; Jianqing Lin; et al. (Journal of Hazardous Materials, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Multi-objective Joint Optimization Operation of Cascade Reservoirs Considering River Hydrological Health Assessment - Chongxun Mo; Zihan Lin; Na Li; Xiaoyu Wan; Gang Tang; Yi Huang (Water Resources Management, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

Editorial Expression of Concern: Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2026)

Paeoniflorin attenuates hyperprolactinemia by targeting the pituitary mPRα-mediated, dopamine receptor-independent signaling in vivo and in vitro - Bingqi Lin; Yun Yi; Xiaolan Mo; Yifan Yang; Yuhao Li; Chunxia Wang; Yuanyi Wei (Toxicology and Applied Pharmacology, 2025)

Screening, synthesis and anti-fatigue function verification of selenopeptides - Lin Shi; Wei Jia; Rong Zhang; Haizhen Mo (Food Research International, 2025)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

Spotted knifejaw (Oplegnathus punctatus) TARBP2 negatively regulates type I IFN responses to promote RGNNV replication - Yijie Lin; Weifu Mo; Xinyu Liao; Minyao Bi; Siting Wu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2025)

Hydrological connection restoration may contribute more than species selection to organic carbon stock accumulation in mangrove - Qijuan Cao; Yuting Yang; Yan Lin; Lingling Zhong; Yutong Jin; Yujia Tian; Yuxi Chen; Luojian Mo; Yisheng Peng (Estuarine, Coastal and Shelf Science, 2025)

Concentration, speciation and origin of lead (Pb) in alluvial agricultural soils in the world’s largest continuous karst terrain, southwestern China - Zhixuan Han; Yifan Liu; Yuhong Mo; Ruiwei Zhao; Yuqun Cai; Shen Huang; Xiaolong Lin (Environmental Geochemistry and Health, 2025)

Self-repair mechanisms of spiking neuron–astrocyte networks in working memory under diverse injury conditions - Bingyi Mo; Xiaoqian Liu; Lin Li; Shanshan Cheng; Yuan Zhu; Ming Yi; Lulu Lu (Cognitive Neurodynamics, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Stereoelectroencephalography in temporal lobe epilepsy: clinical characteristics, influential factors, and surgical outcomes - Jiajie Mo; Xiu Wang; Xuemin Zhao; Baotian Zhao; Chao Zhang; Lin Sang; Wenhan Hu; Jianguo Zhang; Gerold Baier; Xiaoqiu Shao; Kai Zhang (Science Bulletin, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

Single brand tire wear particles promote toxin-producing of an invasive cyanobacterium - Yuanyuan Mo; Jingxiang Lin; Xi Li; Hans-Peter Grossart; Lifeng Lin; Mekiso Y. Sido; Jun Yang (Environmental Research, 2025)

Regulating the morphological structure of cellulose acetate ultrafiltration membrane by adjusting the ratio of N, N-dimethylacetamide: N-methyl pyrrolidone in co-solvent to enhance separation and anti-fouling performance - Minfu Mo; Yaling Lin; Danni Lin; Xiaojuan Ma; Yubin Hong; Lihui Chen; Dong Wang; Liulian Huang (Desalination, 2025)

Influences of sub-zero temperature on dynamic tensile behavior of rhyolite porphyry - Zilong Zhou; Fanjunhui Mo; Xin Cai; Chu Wang; Chunping Lin; Yuanping Lai; Shaohui Tang; Zhongkang Wang (Cold Regions Science and Technology, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Bioremediation of heavy metals by mangrove rhizosphere microbes: Extracellular adsorption mechanisms and enhanced performance of immobilized Aestuariibaculum sp. JKB11 - Zuye Zhang; Xiaojun Huang; Si Chen; Ying Xu; Yue Qiao; Runmei Jia; Song Zhang; Wenting Lin; Xian Jiao; Mo Shi; Huirong Chen; Zhipeng Guo; et al. (Journal of Hazardous Materials, 2025)

Polyacrylonitrile (PAN) electrospun nanofibrous membrane for removing indoor gaseous phthalates: A health-driven framework for macro-channel adsorption module design and its implications - Yu Sun; Donghui Mo; Lvyan Lin; Hongyi Wang; Jianping Cao; Zhongming Bu (Journal of Hazardous Materials, 2025)

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

The antibacterial activity and metabolomic analysis of the recombinant lectin protein PFL-96 derived from Pinctada fucata against Streptococcus agalactiae isolated from tilapia (Oreochromis niloticus) - Xiaojian Mo; Wenyue Li; Jianbing Liu; Qiting Li; Zhongxiu Liang; Xinyu Liang; Jiaxing Tang; Jiahui Liang; Jiang Lin; Peng Liu (Fish & Shellfish Immunology, 2025)

Microemulsion-assisted synthesis of Mn-TCPP@MnxOy heterostructures for enhanced photodynamic therapy via O2 self-production and GSH-activatable imaging - Chan Yang; Yanling Zhao; Yanru Qin; Zihan Yan; Ziyi He; Nan Yang; Liuting Mo; Weiying Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Metallothioneins protect against isoconazole nitrate-induced antitumor activity through the maintenance of cellular redox homeostasis in hepatocellular carcinoma - Chun-fen Mo; Ya-ruo Lei; Jun Lin; Yi Liu; Zhi-wei Zhao; Wen-jing Xiao; Wen-bai Yan; Wei-wei Zhang (Chemico-Biological Interactions, 2025)

Enhancing arcade detection using bi-directed scene graphs with graph convolutional networks on street view imagery - Yi-Wen Mo; Chiao-Ling Kuo; Zhi-Sheng Lin (Remote Sensing Applications: Society and Environment, 2025)

Per- and polyfluoroalkyl substances mixture impairs intestinal barrier function through microbiota-derived 21-deoxycortisol and cortisol metabolism dysregulation - Tingting Lin; Luyang He; Sishuo Liu; Yahui Li; Zhi Huang; Delei Cai; Yiming Wang; Zhe Mo; Yi Zhu; Zhijian Chen; Peiwei Xu; Xiaoming Lou; et al. (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Hierarchical iron phosphides@hard carbon composite cathodes for phenol degradation by highly efficient heterogeneous electro-Fenton - Lizheng Yang; Jiayang Lin; Jiayang Mo; Yingxin Wang; Chenhao Liang; Yanbo Chen; Qilun Huang; Dongying Hu; Xiurong Li (Journal of Cleaner Production, 2025)

PTPN2 modulates antiviral immunity in grouper by promoting TBK1 degradation and suppressing interferon signaling - Xinyu Liao; Yijie Lin; Weifu Mo; Siting Wu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2025)

Zero-valent Fe and MnSO4 collectively stimulate the degradation-related functionalities in the bacterial secretome affecting the efficient degradation of lignocellulose during composting - Xiaolin Lu; Qiqiang Zhang; Shangyu Lin; Rongchun Huang; Yinfeng Yang; Naiguo Mo; Shasha Liang; Guangsheng Qin; Qunliang Li (Chemical Engineering Journal, 2025)

Versatile fabrication of hydrogel coatings with shell powder as a key Ingredient - Feng Li; Jianwan Lin; Yongqi Li; Shijia Wu; Cha Wen; Mengting Mo; Linfeng Huang; Ning Qing; Zhenpin Lu; Xing Jiang; Liuyan Tang (Chemical Engineering Journal, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Sulfonamide-linked π-conjugated carbon nitride with enhanced intramolecular carrier generation and transfer for efficient photocatalysis - Jiajun Fu; Si Chen; Xuanhui Lin; Zongrui Li; Zhao Mo; Mingyue Dong; Zhigang Chen; Hui Xu (Journal of Environmental Chemical Engineering, 2025)

Optimizing application strategies of prohexadione-calcium·uniconazole composite regulator to improve lodging resistance and grain yield in rice cultivation in East China - Dengke Ma; Yimin Ding; Yifan Liu; Lin Du; You Mo; Ali Dai; Junyan Xu; Dalu Gu; Liusheng Duan; Weiming Tan (Field Crops Research, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

New insights into the effects of PFOS exposure on rat lung development: morphological, functional, and single-cell sequencing analysis - Jiali Mo; Jingye Zuo; Lin Yu; Huishan Zhang; Shuting Weng; Leping Ye (Archives of Toxicology, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Structural characteristics of global virtual water network driven by food consumption in the Belt and Road Initiative region - Qiumeng Zhong; Jiajing Pan; Zehan Lin; Yumeng Li; Xin Mo; Pan He; Xin Cao; Sai Liang (Resources, Conservation and Recycling, 2025)

Mussel-inspired integrated functional 3D printed scaffolds with molybdenum disulfide nanoflowers for tumor therapy and bone reconstruction - Lan Li; Rongcan Wu; Ruchen Hong; Xiaolong Chen; Tingting Huang; Siyi Huang; Xianglei Mo; Zhiyi Wang; Wenge Liu; Yanjin Lu; Ye Wu; Jinxin Lin (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Discovery of novel benzbromarone derivatives via the closed metabolic site as potent human uric acid transporter 1 (URAT1) inhibitors - Wenfeng Ye; Mingchao He; Gaofeng Lin; Li Shao; Jiajia Mo; Yan Zhao; Xiaodong Ma; Qinlong Xu; Zhaoxing Chu (Medicinal Chemistry Research, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Distribution of long-chain polyunsaturated fatty acids and the effects of molasses on DHA production in Thraustochytrium sp. 26185 - Xi Xie; Ziwei Guo; Qinghua Mo; Junkai Luo; Li Lin; Huifan Liu; Gengsheng Xiao; Qin Wang (Algal Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Antibacterial activity of zinc oxide nanoparticles against Shewanella putrefaciens and its application in preservation of large yellow croaker (Pseudosciaena crocea) - Mengqing Liu; Yuhan Mo; Zheyun Dong; Huicheng Yang; Bangchu Lin; Yongyong Li; Yongjiang Lou; Shiqian Fu (Food Research International, 2025)

Machine learning-enhanced low-hysteresis conductive auxetic strain sensors with curved re-entrant honeycomb structures based on MXene/graphene for human rehabilitation training - Weibin Zhu; Xiaojuan Mo; Zhen Wang; Haiqing Liu; Jian Chen; Lin Wang; Dahua Shou (Chemical Engineering Journal, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Ligand engineering boosts catalase-like activity of gold nanoclusters for cascade reactions combined with glucose oxidase in ZIF-8 matrix - Yi-Shu Wang; Chen Dong; Li Zou; Lin Zhao; Jian-Hua Qin; Hui-Lin Mo (Analytica Chimica Acta, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Nonlinear finite element model updating and fourier neural operator for digital twin of reinforced concrete containment vessel under seismic excitations - Si Fu; Chang-Ching Chang; Chawit Kaewnuratchadasorn; Jiaji Wang; Chiun-Lin Wu; Yi-Lung Mo; Thomas T.C. Hsu (Engineering Structures, 2025)

Cascade energy transfer endows phosphorescent carbon dots-based films with tunable and broadband afterglow for fingerprint recognition and anticounterfeiting - Zhanpeng Liu; Xiangbo Ding; Lin Cai; Yihan Jia; Xia Ran; Zhongzheng Guo; Dan Mo; Yatao Pan; Lijun Guo (Chemical Engineering Journal, 2025)

Revealing synergistic mechanisms of biochar-assisted microbial electrolysis cells in enhancing the anaerobic digestion performance of waste activated sludge: Extracellular polymeric substances characterization, enzyme activity assay, and multi-omics analysis - Dunjie Li; Qian Ping; Rongrong Mo; Wenjie Guo; Shuang Zhang; Lin Wang; Yongmei Li (Water Research, 2024)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

The predominant role of IgM in grouper (Epinephelus coioides) mucosal defense against ectoparasitic protozoan infection - Zequan Mo; Huajian Lin; Xueli Lai; Pengbo Dan; Huicheng Wu; Xiaochun Luo; Xueming Dan; Yanwei Li (Fish & Shellfish Immunology, 2024)

Metal-organic framework-sealed heterogeneous nanoenzyme: A dual-mode core–shell sensor for sensitive determination of the chlorpyrifos residue in environment and bioaccumulation in food - Jintong Liu; Jie Tang; Yanyang Mo; Lin Zhou; Tingting Cai; Hong Yang (Chemical Engineering Journal, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

Mycobacterium marinum mediates regulation of prostaglandin E2 expression on host immune response through cyclooxygenase pathway - Dongzi Lin; Bingyao Lin; Xuezhi Wang; Cheng Xu; Liyi Mo; Yanwen Luo; Honghong Tian; Lei Zhou; Zhenhua Chen (Molecular Biology Reports, 2024)

Native CRISPR-Cas-based programmable multiplex gene repression in Klebsiella variicola - Zhifeng Mo; Siying Lin; Ting Li; Guohui Yu; Yunhao Sun; Jianuan Zhou; Zeling Xu (Biotechnology Letters, 2024)

The obesity loss effect of returns to education from urban–rural and gender perspective: evidence from China - Zongshuo Yin; Shijiu Yin; Lin Zhou; Mo Chen; Nianyu Du; Kai Li (Environment, Development and Sustainability, 2024)

Remote sensing inversion of suspended particulate matter in the estuary of the Pinglu Canal in China based on machine learning algorithms - Jinying Mo; Yichao Tian; Jiale Wang; Qiang Zhang; Yali Zhang; Jin Tao; Junliang Lin (Frontiers in Marine Science, 2024)
Introduction Suspended particulate matter (SPM) is a critical indicator of water quality and has a significant impact on the nearshore ecological environment. Consequently, the quantitative evaluation of SPM concentrations is essential for managing nearshore environments and planning marine resources. Methods This study utilized Sentinel-2’s single band and water index variables to develop a remote sensing inversion model for oceanic SPM in the estuary of the Pinglu Canal in China. Six machine learning algorithms were employed: K-nearest neighbor regression (KNNR), AdaBoost regression (ABR), random forest (RF), gradient boosting regression (GBR), extreme gradient boosting regression (XGBR), and light generalized boosted regression (LGBM). The model with the optimal performance was then selected for further analysis. This research applied the established model to investigate the spatial-temporal dynamics of SPM from 2021 to 2023. Results The findings indicated that (1) the XGBR algorithm exhibited superior performance (R 2 = 0.9042, RMSE = 3.0258 mg/L), with LGBM (R 2 =0.8258, RMSE = 4.0813 mg/L) and GBR (R 2 = 0.823, RMSE = 4.3477 mg/L) also demonstrating effective fitting. However, the ABR, RF, and KNNR algorithms produced less satisfactory fitting results. (2) Additionally, the study revealed that the combination of input variables in the XGBR algorithm was more accurate than single-variable inputs. (3) The contribution of single-band variables to the XGBR algorithm surpassed that of water index variables, with B12, B4, and B11 emerging as the top three influential variables in the model. (4) The annual SPM concentration in the study area exhibited an overall increasing trend, while its spatial distribution generally decreased from the estuary toward the Maowei Sea and Qinzhou Bay. Discussion The combination of Sentinel-2 data and XGBR model has shown good performance in retrieving SPM concentration, providing a new method and approach for large-scale estimation of SPM concentration.

Pancreatic cancer-derived exosomal miR-510 promotes macrophage M2 polarization and facilitates cancer cell aggressive phenotypes - Tao Wang; Lin Ye; Yingjie Zhou; Xionghan Zhang; Renjian Li; Yi Zhou; Jun Weng; Qingrong Mo; Yaqun Yu (Human Cell, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Improving peanut growth and cadmium phytoextraction capacity by inoculating Bacillus megaterium and Trichoderma harzianum - Jie Xiong; Dongsheng Zou; Jianguo Kang; Yingying Mo; Lin Li; Likun Zhan; Qingdan Wu; Zhihua Xiao (Journal of Environmental Management, 2024)

Integrating DNA logic computation and Self-Replication on nanospheres for amplified detection of Dual miRNAs - Liuting Mo; Yan Hong; Rongzheng Yuan; Mingxiu Mo; Chan Yang; Weiying Lin (Chemical Engineering Journal, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Multimodal enhancement of ferroptosis for synergistic cascade colorectal cancer therapy - Ziying Wu; Kun Chen; Weisheng Mo; Yue Wang; Xiewei Lin; Zhien Lan; Caijing Mo; Haocheng Wang; Xiaoying Li; Xingdi Fan; Hungchen Chen; Zhilin Shu; et al. (Chemical Engineering Journal, 2024)

Upcycling of Pb from lead smelting residues to lead halide perovskite for piezocatalytic hydrogen production - Xiaofeng Mo; Mengye Wang; Han Song; Jie Li; Zhen Wu; Zhang Lin (Chemical Engineering Journal, 2024)

Novel nano-capsule for targeted drug delivery and real-time therapeutic monitoring in osteosarcoma treatment - Chen Zhao; Mo Ma; Jukun Yang; Lin Liu; Pinyi Ma; Qiong Wu; Daqian Song (Chemical Engineering Journal, 2024)

VfLRR-RLK1 benefiting resistance to Fusarium oxysporum reveals infection and defense mechanisms in tung tree - Haibo Wu; Wanzhen Mo; Yanli Li; Lin Zhang; Yunpeng Cao (Physiology and Molecular Biology of Plants, 2024)

Allelopathy research on the continuous cropping problem of poplar (populus) - Tao Song; Jia-Xu Chen; Lin-Miao Shan; Yu-Chen Qian; Mo-Xian Chen; Jian-Gang Han; Fu-Yuan Zhu (Phytochemistry Reviews, 2024)

Structure-Functional Activity of Pyrone Derivatives for Inhibition of Barnacle Settlement and Biofilm Formation - Mo Aqib Raza Khan; Bo-Wei Wang; Hsiu-Chin Lin; Yu-Liang Yang; Chih-Chuang Liaw (Marine Biotechnology, 2024)

Assessment of the Safety and Exopolysaccharide Synthesis Capabilities of Bacillus amyloliquefaciens D189 Based on Complete Genome and Phenotype Analysis - Wenfeng Mo; Hailin He; Yifei Mo; Yongyi Lin; Xiaowen Ye; Li Huang; Shubo Li (Current Microbiology, 2024)

Bird detection and overall bird situational awareness at airports - Hongxuan Fu; Chunyi Wang; Nihed Benani; Mingqi Zhang; Jian Lin Chen; Yanqi Gong; Xunqiang Mo; Jinjing Gao; Guozhu Mao (Ornithology Research, 2024)

Simultaneous efficient removal of tetracycline and mitigation of antibiotic resistance genes enrichment by a modified activated sludge process with static magnetic field - Yuan-Mo Zhu; Yongsheng Chen; Hewei Lu; Kai Jin; Yuan Lin; Hongqiang Ren; Ke Xu (Water Research, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Glycerophospholipid metabolism changes association with ozone exposure - Yi Zhang; Jicheng Gong; Xinyan Hu; Linchen He; Yan Lin; Junfeng Zhang; Xin Meng; Yinping Zhang; Jinhan Mo; Drew B. Day; Jianbang Xiang (Journal of Hazardous Materials, 2024)

pH-dependent mechanisms of sulfadiazine degradation by natural pyrite-driven heterogeneous Fenton-like reactions - Xiaoxuan Lin; Jinwen Hu; Zhihua Mo; Zhen Wang; Ruyi Wang; Jialin Liang (Journal of Environmental Management, 2024)

The sensing of circRNA with tetrahedral DNA nanostructure modified microfluidic chip - Shiliang He; Lei Chen; Zhuolang Chen; Guihao Zhang; Yongjin Huang; Huaxiao Zheng; Qing Yang; Zhuoxi Mo; Xinyi Lin; Jiancheng Wen (Analytica Chimica Acta, 2024)

Antioxidant peptide ETT from Isochrysis zhanjiangensis attenuate skin aging by maintaining homeostasis and promoting collagen generation - Yuan-Lin He; Yi Liu; Liyuan Lin; Yinhuan Mo; Huijuan Li; Chunxia Zhou; Pengzhi Hong; Zhong-Ji Qian (Algal Research, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Solid-state fermentation of Limosilactobacillus fermentum and lysine addition to improve the cooking and eating quality of high-fiber rice noodles - Yakun Song; Jing Lin; Lijuan Luo; Zihan Chen; Weiling Mo; Xiangjin Fu; Chun Liu (Journal of Cereal Science, 2024)

Plant-Cell mediated synthesis of MnCo2O4 nanoparticles and their activation of peroxymonosulfate to remove Tetracycline - Jialu Ji; Qi Zhang; Hesu Mo; Zhongfei Ren; Yan Lin; Zhigang Chen; Tiina Leiviskä; Zhengying Wu (Chemical Engineering Journal, 2024)

Sulfated cellulose nanofibrils-based hydrogel moist-electric generator for energy harvesting - Jilong Mo; Xijun Wang; Xuejiao Lin; Xiao Feng; Changjing Qiu; Shenming Tao; Pinhong Chen; Kunkun Zhu; Haisong Qi (Chemical Engineering Journal, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

High-throughput analysis of hazards in novel food based on the density functional theory and multimodal deep learning - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Wenwen Bian; Haizhen Mo (Food Chemistry, 2024)

Nitrogen supply neutralizes the nanoplastic-plant interaction in a coastal wetland - Chunping Zhang; Yingchao Lin; Qing Xue; Xunqiang Mo; Mengxuan He; Jie Liu (Environmental Research, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

CO2 fluxes contrast between aquaculture ponds and mangrove forests and its implications for coastal wetland rehabilitation in Leizhou Peninsula, China - Ruikun Gou; Jianxiang Feng; Haichao Zhou; Tao Lang; Jiayu Zhao; Lidong Mo; Shanshan Song; Guanghui Lin (Agriculture, Ecosystems & Environment, 2024)

IFITM1 and IFITM2 inhibit the replication of senecavirus A by positive feedback with RIG-I signaling pathway - Huizi Li; Ming Chen; Tingting Zheng; Xiaoling Lei; Cunhao Lin; Shuo Li; Jiacong Mo; Zhangyong Ning (Veterinary Microbiology, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Interactions and coupling mechanisms between Anammox, partial denitrification (PD) and hydroxyapatite (HAP) biomineralization in a PD/A-HAP system - Haozhe Mo; Lan Lin; Qian Zhang; Zikun Zhang; Jih-Gaw Lin; Wenzhi Cao; Yanlong Zhang (Chemical Engineering Journal, 2024)

Behavioral and physiological responses of nocturnal marine shellfish to predation pressure - Qi Luo; Xiaolong Gao; Mo Zhang; Shihui Lin; Huiyang Huang; Miaoqin Huang; Caihuan Ke (Applied Animal Behaviour Science, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Infant Exposure and Risk Assessment of Organophosphorus Flame Retardants in Human Breast Milk from The Southeast City, China - Quan Zhang; Yan Wang; Jianlin Lou; Zeteng Ying; Xunjie Mo; Shu Lin (Exposure and Health, 2024)

Genetic variants in m5C modification genes are associated with survival of patients with HBV-related hepatocellular carcinoma - Bowen Chen; Moqin Qiu; Rongbin Gong; Yingchun Liu; Zihan Zhou; Qiuping Wen; Xiaoxia Wei; Xiumei Liang; Yanji Jiang; Peiqin Chen; Yuying Wei; Qiongguang Huang; et al. (Archives of Toxicology, 2024)

Population parameters and heterogeneity in survival rates of Indo-Pacific humpback dolphins in a heavily urbanized coastal region of southeast China: implications for conservation - Wenzhi Lin; Leszek Karczmarski; Stephen C. Y. Chan; Ruiqiang Zheng; Yuen-Wa Ho; Yaqian Mo (Frontiers in Marine Science, 2024)
The Pearl River Delta (PRD) region on the southeast coast of China is among the largest and most populated metropolitan regions of the world, subjecting the Indo-Pacific humpback dolphins ( Sousa chinensis ) inhabiting coastal waters of this region – apparently the largest population of this species – to intense anthropogenic pressure. In this 5-year study (2011-2015), we applied mark-recapture techniques to quantify population parameters of humpback dolphins in the main body of the extensive estuarine system of the Pearl River, the Lingding Bay (LB), the most urbanized and industrialized part of PRD. The super-population size was estimated at 928 individuals (95% CI=823-1046), which however over-represents the latest number of extant animals. Annual estimates fluctuated between 708 and 750 dolphins, and likely reflect most accurately the latest/current number of humpback dolphins in waters of LB. Both the overall and annual estimates generated by our study are considerably lower than previously published abundance estimates. Apparent survival rates were generally low, estimated at 0.943 (SE = 0.008, 95% CI = 0.929-0.958) and 0.815 (SE = 0.025, 95% CI = 0.766-0.866) for adults and juveniles, respectively. In conjunction with limited recruitment, they may have led to a substantial decline in population numbers over the past two decades. Notably, dolphins exhibited heterogeneous apparent survival rates across the complex anthropogenic seascape of LB. Adult individuals that use Hong Kong waters as their primary habitat exhibited 6.2% higher survival rates than those in other parts of LB. This difference tripled (19.2%) for juveniles, a likely expression of their susceptibility to environmental and/or anthropogenic stresses. We suggest that the difference in survival is largely due to heterogeneous anthropogenic stressors that vary spatially across the estuary, among which habitat loss, pollution, and declining prey resources appear to be the primary threats. Based on our latest findings, we call for a strategic conservation planning with the highest priority given to preserve the remaining key dolphin habitats in Hong Kong waters, and to quantify and mitigate the impacts of major stressor(s) in Guangdong (mainland China) waters. Given the encroachment of ever-more-intense human activities on the coastal habitats of humpback dolphins, understanding their demographic response and the underlying mechanisms of the population processes may prove instrumental in the formulation of a conservation management strategy that can secure their continuous survival.

Effects of flow velocity on the muscle nutrient content and flesh quality of the Pacific abalone (Haliotis discus hannai) - Shihui Lin; Mo Zhang; Qi Luo; Miaoqin Huang; Caihuan Ke; Xiaolong Gao (Aquaculture, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Atmospheric water demand constrains net ecosystem production in subtropical mangrove forests - Ruikun Gou; Jinshu Chi; Jiangong Liu; Yunpeng Luo; Ankit Shekhar; Lidong Mo; Guanghui Lin (Journal of Hydrology, 2024)

Targeting Ferroptosis Promotes Functional Recovery by Mitigating White Matter Injury Following Acute Carbon Monoxide Poisoning - Shuhong Wang; Binyuan Xiong; Yin Tian; Quan Hu; Xuheng Jiang; Ji Zhang; Lin Chen; Ruilie Wang; Mo Li; Xin Zhou; Tianxi Zhang; Hongfei Ge; et al. (Molecular Neurobiology, 2024)

Optimization of the manufacturing process and properties of alkali-activated palm oil fuel ash-based cold-bonded aggregates - Jiayi Lin; Tee How Tan; Jerome Song Yeo; Yingxin Goh; Tung-Chai Ling; Kim Hung Mo (Journal of Cleaner Production, 2024)

Determination of uptake rates of volatile organic compounds by 24-hour passive sampling and their application in enclosed ship cabin environments - Tao Yu; Yan Wang; Longfei Chen; Wenjun Leng; Yue Shi; Bencheng Lin; Juntao Zhao; Zhiyuan Wang; Jinhan Mo; Cong Liu (Building and Environment, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Thermal bleaching in the northern South China Sea: impact of abnormal environment and climate on high-latitude coral reefs - Xin Wang; Yinqiang Li; Mingqing Lin; Zhiwei Che; Weihua Mo; Yanli Chen; Shaohua Mo; Wentao Niu; Haolang Zhou (Environmental Science and Pollution Research, 2023)

Association between multiple metals exposure and sleep disorders in a Chinese population: A mixture-based approach - Lu Yufu; Liu Qiumei; Zhang Tiantian; Cai Jiansheng; Tang Xu; Wei Yanfei; Mo Xiaoting; Huang Shenxiang; Lin Yinxia; Li You; Luo Tingyu; Qin Jian; et al. (Chemosphere, 2023)

Adulteration of endogenous substances as a next challenge in dairy safety: High-throughput analysis of flavours in goat milk based on the molecular mechanism of flavouring components dynamic changes - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Haizhen Mo (Trends in Food Science & Technology, 2023)

Ecological benefits of artificial light at night (ALAN): Accelerating the development and metamorphosis of marine shellfish larvae - Mo Zhang; Xiaolong Gao; Qi Luo; Shihui Lin; Mingxin Lyu; Xuan Luo; Caihuan Ke; Weiwei You (Science of The Total Environment, 2023)

N-doped porous carbon material derived by MOFs calcined in proper oxygen atmosphere as high-performance catalyst for the low-temperature NH3-SCR - Jiexuan Zhu; Donghai Mo; Lin Tao; Jinfeng Li; Shiying Fu; Lihui Dong; Bin Li; Zhengjun Chen; Minguang Fan (Journal of Environmental Chemical Engineering, 2023)

Temporal variations of carbon and water fluxes in a subtropical mangrove forest: Insights from a decade-long eddy covariance measurement - Ruikun Gou; Nina Buchmann; Jinshu Chi; Yunpeng Luo; Lidong Mo; Ankit Shekhar; Iris Feigenwinter; Lukas Hörtnagl; Weizhi Lu; Xiaowei Cui; Yuchen Meng; Shanshan Song; et al. (Agricultural and Forest Meteorology, 2023)

Novel amino-modified bamboo-derived biochar-supported nano-zero-valent iron (AMBBC-nZVI) composite for efficient Cr(VI) removal from aqueous solution - Xiaobin Zhou; Yingxue Wang; Huili Liu; Yanan Zhang; Yinming Fan; Shengpeng Mo; Huaxia Li; Junyi Wang; Hua Lin (Environmental Science and Pollution Research, 2023)

Circadian feeding characteristics of different abalone species and construction of a gastrointestinal evacuation model - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Caihuan Ke (Aquaculture, 2023)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Examination of the effects of blue light stress on monoamine oxidase-mediated immunomodulatory function in the Pacific abalone, Haliotis discus hannai - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2023)

Enhancing alkali-activated materials with low quality fly ash: A novel mixing approach for robust construction materials - Reza Mirmoghtadaei; Lin Shen; Yanping Li; Mo Li; Baomin Wang (Journal of Cleaner Production, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Physical enrichment for improving welfare in fish aquaculture and fitness of stocking fish: A review of fundamentals, mechanisms and applications - Zonghang Zhang; Wuhan Lin; Yunqi Li; Xianyu Yuan; Xianqing He; Hancheng Zhao; Jiezhang Mo; Jianqing Lin; Liangliang Yang; Bo Liang; Xiumei Zhang; Wenhua Liu (Aquaculture, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Comprehensive analysis of a novel power and methanol coproduction process using landfill gas reforming and renewable hydrogen generation by an alkaline electrolyzer - Haitao Lin; Mo Han Zhang; Bhupendra Singh Chauhan; Awatif M.A. Elsiddieg; Mohamed Abdelghany Elkotb; Peng Zhu; Ruicheng Tian; Mohamed Abouelela (Journal of Cleaner Production, 2023)

Spatial variation in the community structure and response of benthic macroinvertebrates to multiple environmental factors in mountain rivers - Zaoli Yang; Shufeng He; Tao Feng; Yuqing Lin; Mo Chen; Qinyuan Li; Qiuwen Chen (Journal of Environmental Management, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Nano-Priming with La2O3 Improves Early Growth and Regulates Physio-Biochemical Mechanisms in Fragrant Rice Against Cadmium Toxicity - Feiyang Sun; Weifen Chen; Yong Ren; Siren Cheng; Umair Ashraf; Jiewen Zheng; Li Lin; Yixian Ma; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2023)

Association of CYP19A1 Gene, Plasma Zinc, and Urinary Zinc with the Risk of Type 2 Diabetes Mellitus in a Chinese Population - Xuexiu Wang; Yujian Liang; Qiumei Liu; Jiansheng Cai; Xu Tang; Shuzhen Liu; Junling Zhang; Min Xu; Chunmei Wei; Xiaoting Mo; Yanfei Wei; Yinxia Lin; et al. (Biological Trace Element Research, 2023)

Impact of rhizosphere priming on soil organic carbon dynamics: Insights from the perspective of carbon fractions - Hao Cui; Chaoyang Mo; Pengfei Chen; Rui Lan; Chao He; Jingdong Lin; Zhenhui Jiang; Jingping Yang (Applied Soil Ecology, 2023)

Development of Au8 nanocluster-based fluorescent strip immunosensor for sensitive detection of aflatoxin B1 - Zi-Hui Shao; Aoqiang Zhai; Yue Hua; Hui-Lin Mo; Fuwei Xie; Xueli Zhao; Ge Zhao; Shuang-Quan Zang (Analytica Chimica Acta, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Controlling Diels-Alder reactions in catalytic pyrolysis of sawdust and polypropylene by coupling CO2 atmosphere and Fe-modified zeolite for enhanced light aromatics production - Yao He; Junjie Chen; Ziming Mo; Changsong Hu; Detao Li; Jianhua Tu; Chen Lin; Yi Wang; Dongxia Liu; Tiejun Wang (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Incorporation of spring maize into paddy fields increased nitrogen uptake in late rice by enhancing soil nitrogen supply: Field 15N tracer studies - Zhenhui Jiang; Hao Cui; Jingdong Lin; Chaoyang Mo; Yizhen Liu; Yongfu Li; Jingping Yang (Field Crops Research, 2023)

miR-4299 inhibits tumor progression in pancreatic cancer through targeting ADAM17 - Junhong Liu; Lin Ye; Kangqiang Lin; Tieshan Zhong; Jiguang Luo; Tao Wang; Liya Suo; Qingrong Mo; Shuqun Li; Qian Chen; Yaqun Yu (Molecular and Cellular Biochemistry, 2023)

A physical analysis of summertime North American heatwaves - Bin Yu; Hai Lin; Ruping Mo; Guilong Li (Climate Dynamics, 2023)
This study examines the dominant heatwave variability over North America (NA), extracted from an empirical orthogonal function (EOF) analysis of summertime monthly warm extreme index anomalies over 1959–2021. The principal mode features a dipole structure with a large area of anomaly over northwestern NA and an anomaly of opposite sign over the southern U.S. The corresponding principal component is associated with a large-scale atmospheric wave train extending from the North Pacific to North America (NP-NA) and a northeastward injection of moisture from the subtropical western Pacific towards western NA, which are key factors in supporting the NA heatwave variability. The NP-NA wave train can be systematically reinforced and supported by synoptic-scale eddies, and may also be forced by an anomalous convection over the tropical-subtropical western Pacific. Surface radiation heating directly contributes to surface temperature anomalies and is dominated by anomalous downwelling shortwave and longwave radiations. In association with a positive phase of the heatwave variability, the NP-NA wave train brings an anticyclonic anomaly over northern NA, leading to anomalous descent, reduced total cloud cover and below-normal precipitation and surface relative humidity over northern NA. Over northwestern NA, the anomalous subsidence causes air to warm through compression. Reduced cloud cover results in increased downward shortwave radiation that is a key contributor to surface radiation heating. In addition, increase in vertically integrated water vapour through the moisture injection from the North Pacific collocates with tropospheric warming. The atmosphere has more water vapor holding capability and acts as a greenhouse gas to absorb longwave radiation, leading to increased downward longwave radiation that is the second major contributor to surface radiation heating. Processes with circulation and surface radiation anomalies of opposite signs will likewise lead to the negative heatwave variability.

Corrigendum to “Association of serum per- and polyfluoroalkyl substances and gestational anemia during different trimesters in Zhuang ethnic pregnancy women of Guangxi, China” [Chemosphere. Dec 2022 309:136798] - Qian Liao; Peng Tang; Dongxiang Pan; Yanye Song; Lei Lei; Jun Liang; Bihu Liu; Mengrui Lin; Huishen Huang; Meile Mo; Chengtuo Huang; Ming Wei; et al. (Chemosphere, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Association between barium exposed, CYP19A1 and central obesity: A cross-sectional study in rural China - Yufu Lu; Lidong Qin; Yanfei Wei; Xiaoting Mo; Xu Tang; Qiumei Liu; Shuzhen Liu; Junling Zhang; Min Xu; Chunmei Wei; Shenxiang Huang; Yinxia Lin; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Associations of Dietary and Plasma Copper Levels with Liver Function in a Chinese Population - Yanfei Wei; Jiansheng Cai; Xiaoting Mo; Min Xu; Qiumei Liu; Junling Zhang; Shuzhen Liu; Yinxia Lin; Shenxiang Huang; Jian Qin; Zhiyong Zhang (Biological Trace Element Research, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

An assessment of the LICOM Forecast System under the IVTT class4 framework - Weipeng Zheng; Pengfei Lin; Hailong Liu; Yihua Luan; Jinfeng Ma; Huier Mo; Juan Liu (Frontiers in Marine Science, 2023)
This paper evaluates LFS (LICOM Forecast System) forecasts and compares them with other marine forecast systems under the IVTT (Intercomparison and Validation Task Team) Class 4 framework. LFS delivers real-time daily forecasts driven by the GFS (Global Forecast System) atmospheric analyses and surface forecasts. The nudging method in LFS provides the initial state for forecasting, with only the temperature and salinity restored towards the Mercator PSY4 daily analyses. Assessments show that LFS demonstrates a reasonably good capability in short-term marine environment forecast. For the leading 1-6 days forecasts, the root mean square error (RMSE) ranges between 0.53-0.63°C, 0.57-0.66°C and 0.12-0.13 psu for the sea surface temperature, temperature, and salinity profiles, respectively. The overall performance is comparable to other major marine forecast systems, with a slight advantage in forecasting the temperature and salinity profiles. Different nudging time scales are applied to the upper ocean and deep ocean to preserve the effects of mesoscale processes and correct the large-scale biases in temperature and salinity. However, the absence of other observational constraints, such as the sea level height, significantly affects the regional forecast features. Further analyses are required to improve the performance, and the integration of an assimilation system into LFS is urgently needed.

Evaluation of in vitro toxicity information for zebrafish as a promising alternative for chemical hazard and risk assessment - Jing Yang; Yolina Yu Lin Wang; Syed Shabi Ul Hassan Kazmi; Jiezhang Mo; Hailin Fan; Yuwen Wang; Wenhua Liu; Zhen Wang (Science of The Total Environment, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Sex-Specific Associations of Urinary Metals with Renal Function: a Cross-sectional Study in China - Yinxia Lin; Jiansheng Cai; Qiumei Liu; Xiaoting Mo; Min Xu; Junling Zhang; Shuzhen Liu; Chunmei Wei; Yanfei Wei; Shenxiang Huang; Tingyu Mai; Dechan Tan; et al. (Biological Trace Element Research, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

High-efficiency removal of Cs (I) by vermiculite/zinc hexacyanoferrate (II) composite from aqueous solutions - Tianya Dai; Jinpeng Feng; Jiann-Yang Hwang; Yangyang Bao; Chenhui Gao; Zeping Wang; Wei Mo; Xiujuan Su; Hongfei Lin (Journal of Environmental Chemical Engineering, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Health effects of exposure to indoor formaldehyde in civil buildings: A systematic review and meta-analysis on the literature in the past 40 years - Ningrui Liu; Lin Fang; Wei Liu; Haidong Kan; Zhuohui Zhao; Furong Deng; Chen Huang; Bin Zhao; Xiangang Zeng; Yuexia Sun; Hua Qian; Jinhan Mo; et al. (Building and Environment, 2023)

Regulation of Growth and Physiological Properties of Fragrant Rice Seedlings by Hydrogen-Rich Water (HRW) Under Nitrogen-Deficient Conditions - Ye Jiang; Qiuyi Ye; Lin Ma; Xiaojuan Yang; Jianwen Zhang; Zhaowen Mo (Journal of Plant Growth Regulation, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Insights into the role of prechlorination in algae-laden raw water distribution process: Algal organic matter and microcystin-LR release, extracellular polymeric substances (EPS) aggregation, and pipeline biofilm communities - Yueting Wang; Hang Xu; Hao Yao; Bonan Liu; Mingmei Ding; Tao Lin; Tianpei Mo; Li Gao; Lei Zhang (Journal of Hazardous Materials, 2023)

Effects of Fe(II)-activated persulfate/sodium percarbonate (PS/SPC) pretreatment on ultrafiltration membrane fouling control and mechanisms - Jiachen Mo; Tao Lin; Xue Zhang; Fuchun Jiang; Han Chen (Desalination, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Association of Dietary and Plasma Magnesium with Glycaemic Markers in a Chinese Population - Min Xu; Jiansheng Cai; Xiaoting Mo; Qiumei Liu; Junling Zhang; Yanfei Wei; Shuzhen Liu; Yinxia Lin; Shenxiang Huang; Chunbao Mo; Tingyu Mai; Dechan Tan; et al. (Biological Trace Element Research, 2023)

Effect of dietary Bacillus subtilis supplement on Cd toxicokinetics and Cd-induced immune and antioxidant impairment of Procambarus clarkii - Caijiao Dai; Lin Xiao; Aijie Mo; Yongchao Yuan; Junfa Yuan; Zemao Gu; Jianghua Wang (Environmental Science and Pollution Research, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Triggered amplification of gene theranostics with high accuracy and efficacy using metallo-nanoassemblies - Jialing Hu; Zhiqiao Zou; Fengye Mo; Xue Lin; Yun Zhao; Tianhui Shi; Fuan Wang; Xiaoqing Liu (Chemical Engineering Journal, 2023)

Normal Closure Behavior of Rock Fractures Considering Transition from Elastic Deformation to Fully Plastic Flow - Lin Huang; Cheng Zhao; Bo Li; Yangyang Mo; Jinquan Xing; Huiguan Chen (Rock Mechanics and Rock Engineering, 2023)

Functionalized photosensitive metal-organic framework as a theranostic nanoplatform for turn-on detection of MicroRNA and photodynamic therapy - Chan Yang; Kun Wang; Shuo Tian; Liuting Mo; Weiying Lin (Analytica Chimica Acta, 2023)

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

Study on aptamer based high throughput approach identifies natural ingredients against RGNNV - Hongling Wei; Mingzhu Liu; Ke Ke; Shuangyan Xiao; Lin Huang; Qiongyu He; Changping Mo; Hai Pang; Guozhu Xiao; Pengfei Li; Qing Yu (Journal of Fish Diseases, 2022)
Nervous necrosis virus (NNV) is one of the most destructive pathogens in marine fish aquaculture and is capable of infecting more than 50 fish species worldwide, which resulted in great economic losses. Effective drugs for managing NNV infection are urgently required. Medicinal plants have been known for thousands of years and benefit of medicinal plants against pathogens in aquaculture have emerged. Nowadays, the most commonly used method for detecting virus infection and assessing antiviral drugs efficacy is reverse transcription‐quantitative real‐time PCR. However, the application is limited on account of high reagent costs, complex time‐consuming operations and long detection time. Aptamers have been widely applied in application of pathogens or diseases diagnosis and treatments because of high specificity, strong affinity, good stability, easy synthesized and low costs. This study aimed to establish an aptamer (GBN34)‐based high‐throughput screening (GBN34‐AHTS) model for efficient selection and evaluation of natural ingredients against NNV infection. GBN34‐AHTS is an expeditious rapid method for selecting natural ingredients against NNV, which is characterized with high‐speed, dram, sensitive and accurate. AHTS strategy could reduce work intensity and experimental costs and shorten the whole screening cycle of effective ingredients. AHTS should be suitable for rapid selection of effective ingredients against other viruses, which is important for improving the prevention and controlling of aquatic diseases.

Feeding strategy trade-off and selection of marine nocturnal gastropods under predation risk - Shihui Lin; Xiaolong Gao; Mo Zhang; Mingxin Lyu; Caihuan Ke (Frontiers in Marine Science, 2022)
The circadian rhythm is one of the most crucial and universal biological rhythms in living organisms. As a typical nocturnal creature, the Pacific abalone ( Haliotis discus hannai ) exhibits rhythmic behaviors in terms of passively selecting whether to avoid predators or to forage, and active adaptation to light cycle changes is regulated by the biological clock. However, no basic data are available to help us to understand these rhythmic behaviors in the abalone species. In the present study, quantification of behavioral data for the abalone and its predator swimming crab Portunus trituberculatus in short-term (24 h) and long-term (40 days) polyculture scenarios suggests that the distance and duration of movement, percentage of feeding individuals, and cumulative duration of feeding of the abalone individuals were significantly lower under the short-term predation risk than the long-term predation risk. The concentrations of 5-hydroxytryptamine (5-HT), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and hexokinase (HK) in hemolymph, and expression levels of 5-HT1A receptor and 5-HT2 receptor in cerebral ganglion were significantly higher under the long-term predation risk than the short-term predation risk. The concentration of lactate dehydrogenase (LDH) and glycogen content in adductor muscle of the abalone was significantly higher under the short-term predation risk than the long-term predation risk, thereby implying their role in anaerobic metabolism and aerobic metabolism as primary energy sources under the short-term and long-term predation risk, respectively. The concentrations of 5-HT and cAMP, and the expression levels of Bmal1 and 5-HT2 receptor exhibited no significant signs of cosine rhythmicity under the short-term predation risk, but changes in the movement and feeding behaviors of the abalone still occurred at the night only. Correlation analysis shows that the expression levels of Bmal1 and Clock had significantly positive correlations with the circadian changes in the movement parameters of the abalone, thereby suggesting a dominant role in the rhythmic expression of endogenous circadian clock genes regulating the rhythmic behavior of the abalone. These findings provide new insights into the origin and evolution of biological rhythms in nocturnal marine animals and a reference for developing rational stock enhancement plans, and would improve protection for marine benthic biodiversity.

NAD+-capped RNAs are widespread in rice (Oryza sativa) and spatiotemporally modulated during development - Haijiao Dong; Xufeng Wang; Cong Tan; Lei Gao; Jie Cui; Lin Liu; Beixin Mo; Yongzhong Xing; Yu Yu; Xuemei Chen (Science China Life Sciences, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Associations Between Plasma Metals and Cognitive Function in People Aged 60 and Above - Junling Zhang; Qiumei Liu; Min Xu; Jiansheng Cai; Yanfei Wei; Yinxia Lin; Xiaoting Mo; Shenxiang Huang; Shuzhen Liu; Chunbao Mo; Tingyu Mai; Dechan Tan; et al. (Biological Trace Element Research, 2022)

Chaperone-mediated Autophagy Regulates Cell Growth by Targeting SMAD3 in Glioma - Hanqun Liu; Yuxuan Yong; Xingjian Li; Panghai Ye; Kai Tao; Guoyou Peng; Mingshu Mo; Wenyuan Guo; Xiang Chen; Yangfu Luo; Yuwan Lin; Jiewen Qiu; et al. (Neuroscience Bulletin, 2022)

Effects of Different Fertilization Methods on Grain Yield, Photosynthetic Characteristics and Nitrogen Synthetase Enzymatic Activities of Direct-seeded Rice in South China - Zheng Zhang; Yifei Wang; Yunyan Chen; Umair Ashraf; Lin Li; Minghua Zhang; Zhaowen Mo; Meiyang Duan; Zaiman Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2022)

miR-183-5p promotes proliferation, invasion, and glycolysis of thyroid carcinoma cells by targeting FOXO1 - Chun Han; Kangnan Mo; Lin Jiang; Kejing Wang; Lisong Teng (Molecular and Cellular Biochemistry, 2022)

Assessment of potential sediment disasters and resilience management of mountain roads using environmental indicators - Chao-Yuan Lin; Yuan-Chung Lai; Shao-Wei Wu; Fan-Chung Mo; Cheng-Yu Lin (Natural Hazards, 2022)
In recent years, extreme rainfall events occur frequently, causing serious watershed sediment disasters, destroying mountain roads, and endangering the safety of residents' lives and property. This study aims to deal with the spatial change of potential sediment movement on the road slope pre-disaster and to screen disaster hot spots for early warning and control system. The conceptual model is used to simulate the distribution of primary and/or derived disasters on a watershed scale to assess the impact of sediment disasters caused by heavy rain event. Correlation analysis shows that the models in assessment of primary disaster and derived disaster are significantly correlated with the collapse ratio and disaster ratio, respectively. Since the primary disaster has been considered when calculating the derived disaster risk, the terrain subdivision along Provincial Highway 21 (Tai-21) is extracted to understand the derived sediment disaster on the road slope. The model can effectively evaluate the road sections prone to disasters. According to the risk level, the hot spot of road slope disasters and the management of disaster resilience are determined and can be the reference for disaster prevention and control.

Characteristics of typical air pollutants in a valley-basin city in South China - Chu Wu; Jibing Li; Xiaoping Lin; Yangzhi Mo; Hui Zhang; Zhihui Liao; Yu Wang; Duohong Chen (Meteorology and Atmospheric Physics, 2022)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1 - Shuang Lin; Xueke Zhang; Ling Shen; Shuyuan Mo; Junjun Liu; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2022)

Long-term changes of water acidity in an intact forested watershed in south China - Xiao-dong Liu; Ying-jie Feng; Qi-feng Mo; Guo-wei Chu; Yue-lin Li; Qian-mei Zhang; Wei-qiang Zhang; Xian-hua Gan; Qing Zhou (Journal of Mountain Science, 2021)

Three new ester glycosides with cytotoxic activity from the seeds of Caesalpinia sappan - Min Wang; Juan Tan; Jun Chen; Tian Xie; Liang-Mo Lin; Li-Li Zhong; Xing-Jun Cai; Qiong-Shi Wu (Natural Product Research, 2021)

Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Ying Su; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai , attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai . Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.

Application of hydrogen-rich water modulates physio-biochemical functions and early growth of fragrant rice under Cd and Pb stress - Lin Ma; Leilei Kong; Runfei Gui; Xiaojuan Yang; Jianwen Zhang; Qi Gong; Dejun Qin; Maosen Zhuang; Umair Ashraf; Zhaowen Mo (Environmental Science and Pollution Research, 2021)

Nuclear-localized eukaryotic translation initiation factor 1A is involved in mouse preimplantation embryo development - Yue Liu; Jiandong Sun; Yang Su; Jianmin Lin; Chengyu Lv; Kaien Mo; Songhua Xu; Shie Wang (Journal of Molecular Histology, 2021)

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
Abalone ( Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms ( P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea , but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai . The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX 2 R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea . These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.

Exogenous Melatonin and Catechol Application Modulate Physio-Biochemical Attributes and Early Growth of Fragrant Rice Under Cd Toxicity - Yuzhan Li; Luxin Liang; Shicong Huang; Wu Li; Umair Ashraf; Lin Ma; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Melatonin and Nitrogen Applications Modulate Early Growth and Related Physio-biochemical Attributes in Maize Under Cd Stress - Lin Ma; Zhuoli Huang; Shuying Li; Umair Ashraf; Wenjing Yang; Hecheng Liu; Daitianshu Xu; Wu Li; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2021)

Common and specific neural correlates underlying insight and ordinary problem solving - Jiabao Lin; Xue Wen; Xuan Cui; Yanhui Xiang; Jiushu Xie; Yajue Chen; Ruiwang Huang; Lei Mo (Brain Imaging and Behavior, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

Natural polyketide 6-pentyl-2 H -pyrone-2-one and its synthetic analogues efficiently prevent marine biofouling - Mo Aqib Raza Khan; Bo-Wei Wang; Yih-Yu Chen; Ting-Hsuan Lin; Hsiu-Chin Lin; Yu-Liang Yang; Ka-Lai Pang; Chih-Chuang Liaw (Biofouling, 2021)

Two new phthalide derivatives from the endophytic fungus Penicillium vulpinum isolated from Sophora tonkinensis - Yuyue Qin; Xiaobo Liu; Jing Lin; Jingying Huang; Xiaofei Jiang; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

A pentatricopeptide repeat protein DUA1 interacts with sigma factor 1 to regulate chloroplast gene expression in Rice - Yanxin Du; Weiping Mo; Tingting Ma; Weijiang Tang; Lijin Tian; Rongcheng Lin (Photosynthesis Research, 2021)

Deep Placement of Nitrogen Fertilizer Affects Grain Yield, Nitrogen Recovery Efficiency, and Root Characteristics in Direct-Seeded Rice in South China - Yunyan Chen; Pingshan Fan; Zhaowen Mo; Leilei Kong; Hua Tian; Meiyang Duan; Lin Li; Liji Wu; Zaimang Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2021)

ERP evidence for asymmetric orthographic transfer between traditional and simplified Chinese - Jiushu Xie; Yanli Huang; Ke Chen; Qian Lin; John X. Zhang; Lei Mo (Experimental Brain Research, 2021)

LncRNA SNHG7 sponges miR-449a to promote pituitary adenomas progression - Xiongfei Yue; Ce Dong; Zhanying Ye; Lin Zhu; Xiaoyang Zhang; Xiaoyan Wang; Feng Mo; Zheng Li; Baogen Pan (Metabolic Brain Disease, 2021)

Straw Incorporation Coupled with Deep Placement of Nitrogen Fertilizer Improved Grain Yield and Nitrogen Use Efficiency in Direct-Seeded Rice - Yunyan Chen; Pingshan Fan; Lin Li; Hua Tian; Umair Ashraf; Zhaowen Mo; Meiyang Duan; Qiantong Wu; Zheng Zhang; Xiangru Tang; Shenggang Pan (Journal of Soil Science and Plant Nutrition, 2020)

Nitrogen Regulates the Grain Yield, Antioxidant Attributes, and Nitrogen Metabolism in Fragrant Rice Grown Under Lead-Contaminated Soil - Huoyi Feng; Yuzhan Li; Yangfan Yan; Xinhang Wei; Yihan Yang; Long Zhang; Lin Ma; Wu Li; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Abundance and residency dynamics of the Indo‐Pacific humpback dolphin, Sousa chinensis , in the Dafengjiang River Estuary, China - Chongwei Peng; Haiping Wu; Xianyan Wang; Qian Zhu; Thomas A. Jefferson; Chun‐Chieh Wang; Youhou Xu; Jian Li; Hu Huang; Mo Chen; Shiang‐Lin Huang (Marine Mammal Science, 2020)
Robust population size estimates are essential for informing population conservation status. Residency dynamics show population habitat use through time. Population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) has been extensively investigated in Chinese waters, but their residency dynamics are rarely known. Mark‐recapture analysis based on photo‐identification records was applied to humpback dolphins in the Dafengjiang River Estuary habitat, one of the key habitats in the northern Beibu Gulf, China. Movement analyses based on lagged identification rate indicated the humpback dolphins spent, on average, 78.5 days inside and 46.9 days outside the survey area. Within the study area, the humpback dolphin abundance was 83 identifiable dolphins. A total of 353–430 humpback dolphins, estimated by POPAN modeling, were involved in this fluid habitat‐use dynamic. Robust Design analysis showed strong seasonality in humpback dolphin abundance and emigration probability, implying a movement‐ and habitat‐use pattern likely associated with spatiotemporal distribution of oceanographic characteristics and prey occurrences. Population surveys and conservation measures currently conducted in Chinese waters seldom consider seasonality in movements between habitat patches, which can be addressed by genetic analyses across habitats and cross‐matching photo‐identification records among neighboring habitats.

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Analysis of Cerebrospinal Fluid Soluble TREM2 and Polymorphisms in Sporadic Parkinson’s Disease in a Chinese Population - Guoyou Peng; Jiewen Qiu; Hanqun Liu; Miaomiao Zhou; Shuxuan Huang; Wenyuan Guo; Yuwan Lin; Xiang Chen; Zhe Li; Guihua Li; Wenlong Zhang; Yunlong Zhang; et al. (Journal of Molecular Neuroscience, 2020)

Dolphin-watching tourism and indo-Pacific humpback dolphins (Sousa chinensis) in Sanniang Bay, China: impacts and solutions - Haiping Wu; Chongwei Peng; Hu Huang; Thomas A. Jefferson; Shiang-Lin Huang; Mo Chen; Qianhui Zeng; Xueying Yu; Xianyan Wang; Youhou Xu (European Journal of Wildlife Research, 2020)

Spatiotemporal assessment of mortality attributable to ambient PM2.5 exposure in Taiwan during 2008–2015 - Su-Lun Hwang; Yu-Ching Lin; Kuang-Yu Hsiao; Chieh-Mo Lin; Miao-Ching Chi (Air Quality, Atmosphere & Health, 2020)

The root transcriptome analyses of peanut wild species Arachis correntina (Burkart) Krapov. & W.C. Gregory and cultivated variety Xiaobaisha in response to benzoic acid and p-cumaric acid stress - Zhong Li; Faqian Xiong; Wenfeng Guo; Changming Mo; Haining Wu; Lin Du (Genetic Resources and Crop Evolution, 2020)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

Akt plays indispensable roles during the first cell lineage differentiation of mouse - Songhua Xu; Lili Pang; Yue Liu; Xiuli Lian; Kaien Mo; Ruimin Lv; Huimin Zhu; Chengyu Lv; Jianmin Lin; Jiandong Sun; Lixuan Xu; Shie Wang (Journal of Molecular Histology, 2019)

Involvement of glutamate receptors in regulating calcium influx in rice seedlings under Cr exposure - Yan-Hong Li; Xiao-Zhang Yu; Ling-Yun Mo; Yu-Juan Lin; Qing Zhang (Ecotoxicology, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Composition and antioxidant and antibacterial activities of essential oils from three yellow Camellia species - Li Ge; Binghui Lin; Jianguang Mo; Qiuhong Chen; Lin Su; Yuejuan Li; Kedi Yang (Trees, 2019)

Ginsenoside Compound K Regulates Amyloid β via the Nrf2/Keap1 Signaling Pathway in Mice with Scopolamine Hydrobromide-Induced Memory Impairments - Qing Yang; Jianan Lin; Huiyuan Zhang; Yingna Liu; Mo Kan; Zhiru Xiu; Xijun Chen; Xingcheng Lan; Xiaohua Li; Xiaozheng Shi; Na Li; Xiaobo Qu (Journal of Molecular Neuroscience, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Effects of fine particulate matter and its constituents on emergency room visits for asthma in southern Taiwan during 2008–2010: a population-based study - Su-Lun Hwang; Yu-Ching Lin; Chieh-Mo Lin; Kuang-Yu Hsiao (Environmental Science and Pollution Research, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Purification and sequence characterization of chondroitin sulfate and dermatan sulfate from fishes - Na Lin; Xiaoli Mo; Yang Yang; Hong Zhang (Glycoconjugate Journal, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Design, synthesis, and antimicrobial activities of new tanshinone IIA esters - Lin-Wei Zeng; Chang-Xin Zhou; Jia-Dong Liu; Chang-Hong Liu; Jian-Xia Mo; A-Fang Hou; Wei Yao; Zhen-Zhen Wang; Li-She Gan (Natural Product Research, 2016)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Dynamics and responses of vegetation to climatic variations in Ziya-Daqing basins, China - Farong Huang; Xingguo Mo; Zhonghui Lin; Shi Hu (Chinese Geographical Science, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Effects of dicyandiamide and dolomite application on N2O emission from an acidic soil - Muhammad Shaaban; Yupeng Wu; Qi-an Peng; Shan Lin; Yongliang Mo; Lei Wu; Ronggui Hu; Wei Zhou (Environmental Science and Pollution Research, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

GSTM1 Null Genotype and GSTP1 Ile105Val Polymorphism Are Associated with Alzheimer’s Disease: a Meta-Analysis - Mo Wang; Yu Li; Lulu Lin; Guijun Song; Teng Deng (Molecular Neurobiology, 2016)

Sleep medicine in Taiwan - Ning-Hung Chen; Liang-Wen Hang; Chia-Mo Lin (Sleep and Biological Rhythms, 2016)

Trends in land surface evapotranspiration across China with remotely sensed NDVI and climatological data for 1981–2010 - X. Mo; S. Liu; Z. Lin; S. Wang; S. Hu (Hydrological Sciences Journal, 2015)

Continuous Treatment of Phenol over an Fe2O3/γ-Al2O3 Catalyst in a Fixed-Bed Reactor - Minghui Lu; Yue Yao; Lulu Gao; Dongmei Mo; Fang Lin; Shuxiang Lu (Water, Air, & Soil Pollution, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Changes of Serum Osteocalcin, Calcium, and Potassium in a Rat Model of Type 2 Diabetes - Lin Xiao; Xian Mo Wang; Tao Yang; Ying Xiong; Zhong Gui Zhang; Jun Ding; Chen Xu; Chang Yuan Xiong (Cell Biochemistry and Biophysics, 2015)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Exploring spatiotemporal patterns and physical controls of soil moisture at various spatial scales - Jianxiu Qiu; Xingguo Mo; Suxia Liu; Zhonghui Lin (Theoretical and Applied Climatology, 2014)

Synthesis and insecticidal activities of N-(5-dehydroabietyl-1,3,4-thiadiazol-2-yl)-benzenesulfonamides - Fangyao Li; Qijin Mo; Wengui Duan; Guishan Lin; Bo Cen; Naiyuan Chen; Zhangqi Yang (Medicinal Chemistry Research, 2014)

Exploring the interannual and spatial variations of ET and GPP with climate by a physical model and remote sensing data in a large basin of Northeast China - Xingguo Mo; Suxia Liu; Dejuan Meng; Zhonghui Lin (International Journal of Climatology, 2014)
Variations in evapotranspiration ( ET ) and gross primary production ( GPP ) due to climatic fluctuations deserve specific considerations for sustainable water and agricultural management. A Vegetation Interface Processes ( VIP ) model assimilated with Terra‐ MODIS remotely sensed leaf area index was used to simulate their spatial and temporal patterns from 2000 to 2010 in the Songhua River Basin of Northeast China at 1‐km grid and 1‐h time step. The predicted ET and GPP were well verified with the eddy covariance measurements, and the ET was in agreement with that derived from water balance. Over the whole basin, average annual precipitation (P), ET , GPP and water use efficiency are 458 mm, 374 mm, 1067 gC m −2 and 2.86 gC m −2 mm −1 , respectively. Both ET and GPP display significantly spatial variability, with ET presenting different and good relationships with precipitation for different kinds of land use covers ( LUCs ); and GPP a unified good relationship across almost all the LUCs except water body. Over the years from 2000 to 2010, Normalized Difference Vegetation Index ( NDVI ), especially crop NDVI , experienced a trend of increasing. GPP showed no significant trend. ET showed an increasing trend for cropland and grassland, a decreasing trend in water body and wetland, no significant trend for other vegetation types and a weakly increasing trend for the whole basin. Annually, ET roughly follows precipitation, whereas GPP was mainly regulated by radiation (Rn). The inter‐annual variability for the eco‐hydrological elements with the order of the coefficient of variation (CV) being P (0.13) > E C (0.055) > ET (0.05) > Rn (0.037) > GPP (0.019) > NDVI (0.01) is less than their spatial variability with the order of CV being E C (0.23) > P (0.22) > GPP (0.19) > ET (0.15) > Rn (0.05). The highest spatial variability of ET and GPP in grassland implies the incurring problem of degradation in western basin. The low spatial variability in paddy relates agricultural management.

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Intercomparison of microwave remote-sensing soil moisture data sets based on distributed eco-hydrological model simulation and in situ measurements over the North China Plain - Jianxiu Qiu; Xingguo Mo; Suxia Liu; Zhonghui Lin; Lihu Yang; Xianfang Song; Guangying Zhang; Vahid Naeimi; Wolfgang Wagner (International Journal of Remote Sensing, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Impacts of climate change on crop evapotranspiration with ensemble GCM projections in the North China Plain - Xingguo Mo; Ruiping Guo; Suxia Liu; Zhonghui Lin; Shi Hu (Climatic Change, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Metal (Pb, Cd, and Cu)-induced reactive oxygen species accumulations in aerial root cells of the Chinese banyan (Ficus microcarpa) - Nan Liu; Zhifang Lin; Hui Mo (Ecotoxicology, 2012)

Assessing Taiwan’s energy security under climate change - Shih-Mo Lin; Jun-Chiang Feng; Fu-Kuang Ko (Natural Hazards, 2012)

Deuterium excess record in a southern Tibetan ice core and its potential climatic implications - Huabiao Zhao; Baiqing Xu; Tandong Yao; Guangjian Wu; Shubiao Lin; Jing Gao; Mo Wang (Climate Dynamics, 2012)

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia - Yao-Chun Hsu; Han-Mo Chiu; Jyh-Ming Liou; Chun-Chao Chang; Jaw-Town Lin; Hui-Hsiung Liu; Ming-Shiang Wu (Cancer Causes & Control, 2012)

Perturbed solving method for interdecadal sea-air oscillator model - Jiaqi Mo; Yihua Lin; Wantao Lin; Lihua Chen (Chinese Geographical Science, 2012)

Matrix metalloproteinase-9 as new biomarkers of severity in multiple organ dysfunction syndrome caused by trauma and infection - Lin Teng; Min Yu; Jun-ming Li; Hua Tang; Jing Yu; Li-hua Mo; Jing Jin; Xian-zhe Liu (Molecular and Cellular Biochemistry, 2012)

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

VereFlu™: an integrated multiplex RT-PCR and microarray assay for rapid detection and identification of human influenza A and B viruses using lab-on-chip technology - Jeanette Teo; Patrizia Di Pietro; Floriana San Biagio; Monica Capozzoli; Yi-Mo Deng; Ian Barr; Natalie Caldwell; Kian-Leong Ong; Mitsuharu Sato; Rosemary Tan; Raymond Lin (Archives of Virology, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Expression, Purification, and Characterization of an Iron Chaperon Protein CyaY from Acidithiobacillus ferrooxidans - Chenbing Ai; Hongyu Mo; Qian Chen; Yuandong Liu; Lin Tang; Juan Du; Jia Zeng (Current Microbiology, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Emergy Assessment of a Wheat-Maize Rotation System with Different Water Assignments in the North China Plain - Shi Hu; Xingguo Mo; Zhonghui Lin; Jianxiu Qiu (Environmental Management, 2010)

Approximate solution for mechanism of thermally and wind-driven ocean circulation - Jiaqi Mo; Wantao Lin; Yihua Lin (Chinese Geographical Science, 2010)

Dissipative travelling wave solution for El Niño tropic sea-air coupled oscillator - Zhaohui Wen; Wantao Lin; Yihua Lin; Jiaqi Mo (Chinese Geographical Science, 2010)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Zearalenone (ZEN) detection by a single chain fragment variable (scFv) antibody - Shi-Hua Wang; Xiao-Yu Du; Ling Lin; Yu-Mo Huang; Zong-Hua Wang (World Journal of Microbiology and Biotechnology, 2008)

Singularly perturbed solution of coupled model in atmosphere-ocean for global climate - Jiaqi Mo; Wantao Lin; Hui Wang (Chinese Geographical Science, 2008)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Estimating the minimum in-stream flow requirements via wetted perimeter method based on curvature and slope techniques - Suxia Liu; Xingguo Mo; Jun Xia; Changming Liu; Zhonghui Lin; Baohui Men; Lina Ji (Journal of Geographical Sciences, 2006)

Variational iteration solving method for sea-air oscillator model of interdecadal climate fluctuations - Jia-qi Mo; Yi-hua Lin; Hui Wang (Chinese Geographical Science, 2005)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Enantioselective production of levofloxacin by immobilized porcine liver esterase - Sang-Yoon Lee; Byung-Hyuk Min; Sung-Ho Hwang; Yoon-Mo Koo; Choul-Kyun Lee; Seong-Won Song; Sun-Young Oh; Sang-Min Lim; Sang-Lin Kim; Dong-II Kim (Biotechnology Letters, 2001)

Longitudinal changes in Ca, Mg, Fe, Cu, and Zn in breast milk of women in Taiwan over a lactation period of one year - Te-Hsien Lin; Yuh-Jyh Jong; Chi-Hsiun chiang; Mo-Hsiung Yang (Biological Trace Element Research, 1998)